Penyuluhan Strategi Peningkatan Penjualan Bagi Pedagang Pasar Sukaramai Medan - Murad Daulay, M. safii; Yunita, Mella; Elyani, Elyani; Fatmasari, Ayunda; Tanjung, Oppie Meisya; Lubis, Hilman (ABDIMASKU : Jurnal Pengabdian Masyarakat UTND, 2025)
This community service program aimed to assist traders at Sukaramai Market in addressing declining sales due to digital competition and the presence of street vendors (PKL). The program focused on providing counseling and assistance in digital marketing strategies to complement traditional offline selling methods. The methods used included preparation, implementation, and evaluation stages. During the preparation stage, observations and interviews were conducted to identify the main challenges faced by the traders. The implementation stage involved interactive counseling by six lecturers and ten students for 35 traders, followed by a practical simulation on creating social media accounts and managing digital promotions. Evaluation was carried out using questionnaires to measure traders' understanding, responses, and readiness to implement the strategies. The results showed that 80% of traders understood the materials presented, with the majority expressing interest in adopting online marketing. Direct assistance enabled most traders to practice the steps of digital marketing independently. However, some challenges were encountered, such as limited internet access and unfamiliarity with technology among a portion of the traders. In conclusion, this program successfully improved traders' understanding and interest in digital marketing as a means to increase their sales. Further training and technological infrastructure support are necessary to expand the program's impact and sustainability. This initiative is expected to provide practical solutions and open opportunities for more adaptive business development in the digital era.